Beyond Use Date (BUD) Determination of Ambroxol Hydrochloride Syrup by High-Performance Liquid Chromatography – UV/VIS Detector - Jatmika, Catur; Iswandana, Raditya; Lestari, Indah Dewi (Pharmaceutical Sciences and Research, 2023)
Ambroxol HCl is a mucolytic agent often used to treat respiratory disorders associated with excess mucus secretion. This study aims to determine the beyond-use date (BUD) of ambroxol HCl syrup on the market based on analysis of the decrease in drug content using High-Performance Liquid Chromatography (HPLC) – UV/Vis detector. The HPLC conditions were reversed-phase with a C18 column, mobile phase containing acetonitrile - phosphate buffer 0.05 M pH 4.5 (60:40) at a flow rate of 1.0 ml/min using UV detection at 248 nm. To determine BUD, five syrup preparations (brands) obtained from the Jakarta area were analyzed in triplicate. The retention time for ambroxol HCl was 4.62 minutes. In the validation, ambroxol HCl showed good linearity with r = 0.99985 in the 6 to 36 µg/ml. LOD and LOQ for ambroxol HCl were 0.74 µg/ml and 2.25 µg/ml, respectively. It is also fulfilled the accuracy and precision parameters with a % recovery from 99.04% to 100.94% and CV<2%. This method meets the requirements according to the ICH Q2(R1) guidelines and can be used for the assay of ambroxol HCl syrup. The ambroxol HCl level on all samples was still higher than 90% (until the 36th day). Normality test data result indicated that data must be divided into two groups that are sample A and B, and sample C, D, and E. In conclusion, the extrapolation result showed that the BUD ambroxol HCl syrup was 83 days for sample A and B, and 49 days for sample C, D, and E.